2015
DOI: 10.1016/j.visres.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of vertical and horizontal fixation disparity in sentence reading

Abstract: Humans have two, frontally placed eyes and during reading oculomotor and sensory processes are needed to combine the two inputs into a unified percept of the text. Generally, slight vergence errors, i.e., fixation disparities, occur but do not cause double vision since disparate retinal inputs fall into Panum's fusional area, that is, a range of disparity wherein sensory fusion of the two retinal images is achieved. In this study, we report benchmark data with respect to the mean magnitude and range of vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…The proportion of alignment for each fixation population further quantifies the role of the vergence system during the reading of multiline texts. Consistent with see also Blythe et al, 2010;Blythe et al, 2006;Jainta et al, 2015;Juhasz et al, 2006;Kirkby et al, 2010;Kirkby et al, 2013;Nikolova et al, 2015;Nikolova et al, 2017Nikolova et al, , 2018, we observed more aligned than unaligned fixations for intraline reading. However, a higher proportion of fixations were unaligned following a return-sweep saccade at fixation onset.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of alignment for each fixation population further quantifies the role of the vergence system during the reading of multiline texts. Consistent with see also Blythe et al, 2010;Blythe et al, 2006;Jainta et al, 2015;Juhasz et al, 2006;Kirkby et al, 2010;Kirkby et al, 2013;Nikolova et al, 2015;Nikolova et al, 2017Nikolova et al, , 2018, we observed more aligned than unaligned fixations for intraline reading. However, a higher proportion of fixations were unaligned following a return-sweep saccade at fixation onset.…”
Section: Discussionsupporting
confidence: 90%
“… 18 Previous studies commonly showed that the horizontal fixation disparity, measured by VOG, had a variance of 2°. 19 , 20 Therefore, monocular viewing was tentatively defined in the present study as a horizontal disparity greater than 2°. The proportion of monocular viewing was calculated using the following formula: monocular viewing time/total reading time.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for a large range of tasks including reading, motor fusion usually serves to reduce disparities and sensory fusion occurs when disparity falls within the functional fusional range (Jainta, Blythe, Nikolova, Jones, & Liversedge, 2014).…”
Section: Sensory Fusion Is Only Possible Within a Limited Range Of Fimentioning
confidence: 99%